Clinical evaluation of root resorption and its correlation with obturation quality in pulpectomized deciduous teeth with different obturating materials: An In vivo study - Gurlal Singh Brar; Nitika Bajaj; Meenu Bhola; Jaskirat Kaur Brar (Wolters Kluwer Medknow Publications, 2019)
Aims and Objectives: The aim was to evaluate the root resorption in pulpectomized deciduous teeth and its correlation with obturation quality using zinc oxide and eugenol (ZOE), Metapex and Endoflas at the interval of 6 and 12 months. Materials and Methods: A total of 150 infected primary mandibular molars were randomly and equally divided into three subgroups (n = 50 each): Group 1 (ZoE), Group 2 (Metapex), and Group 3 (Endoflas) based on the obturation material preferred. The teeth were clinically and radiographically evaluated at 6 and 12 months' postoperatively by another investigator who was blinded to the type of filling material that was used in each tooth. Kruskal-Wallis test, Mann-Whitney Test, and Wilcoxon Signed-Rank Test was used for statistical analysis. Results: When the obturation quality was assessed, the optimal filling was found in 78% of the cases while the rest have underfilling (9%) and overfilling (13%). The incidence of overfilling was higher in the cases with some root resorption. After 12 months, Group 2 showed maximum variation with the highest incidence (70%) of extensive resorption both interradicular and intraradicular (Grade 3 score) followed by Group 1 (26%) and Group 3 (16%), respectively. Conclusion: Among all the materials, Endoflas showed the highest success rate with least incidence of resorption both outside and within the root canal (hollow tube effect) whereas least success rate was observed with Metapex having the hollow tube effect in majority of the cases (70%) after the follow-up of 12 months.